Hybrid control system based on harmonic restraines and reactive compensation - HU GUOQIANG; XIA WEI; KANG JINSONG; CHENG FEI (2015)
The utility model relates to a hybrid control system based on harmonic restraines and reactive compensation, including two current transformer, voltage transformer, the electric current modulate circuit, the voltage modulate circuit, circuit and DSP control panel are caught to the voltage zero passage, a current transformer connects the load side at the electric wire netting, another current transformer connects between inverter circuit and electric wire netting, two current transformer take care of the circuit connection DSP control panel through an electric current respectively, voltage transformer connects on the electric wire netting, and take care of circuit connection voltage zero passage through voltage and catch the circuit, the circuit connection DSP control panel is caught to the voltage zero passage, PWM impulse generator is connected to the DSP control panel, the DSP control panel is TMS320C6000. Compared with the prior art, the utility model discloses the dominant frequency of DSP control panel reaches 300MHz, and electric current traceability is extremely strong, can realize the function of reactive compensation and harmonic suppression simultaneously, the ability of improving the electric energy quality is very good.